Puberty Health Education and Female Students' Self-efficacy - Simin Khatirpasha; Marhamat Farahani-Nia; Soghra Nikpour; Hamid Haghani (Iran University of Medical Sciences, 2019)
Background: Adolescence is an essential period in every human's life. The lack of knowledge on puberty issues may adversely impact an adolescent's future mental health and self-efficacy. The present study aimed to determine the effect of puberty health education on the general self-efficacy of female students. Methods: This was a quasi-experimental study with a pre-test; post-test and a control group design. This study was conducted on 100 female students of public schools with the onset of menstruation in 2018 in Ghaemshahr City, Iran. To prevent data contamination, the control group was selected from another similar public school. The required data were collected by Sherer General Self-efficacy Questionnaire and analyzed by SPSS using statistics, including mean, standard deviation, Chi-squared test, Fisher's Exact test, one-way Analysis of Variance (ANOVA), and Paired Samples t-test. Results: The study groups were matched for demographic variables except for the mother's age (P=0.01) and father's education (P=0.001). Self-efficacy was not low in any of the groups before and after the training. Mean±SD pre-training self-efficacy scores in the intervention (63.68±9.72) and control (65.3±8.78) groups were not statistically significant (P=0.69). Comparing the students' self-efficacy mean Pre-test-Post-test scores revealed a significant difference in the intervention group (P=0.017); however, there was no significant change in the control group (P=0.284) in this respect. Comparing between-group mean self-efficacy changes concerning before and after the intervention values suggested no significant difference (P=0.294). Conclusion: Puberty health education was effective in promoting the explored female students' self-efficacy. Accordingly, it is recommended to include puberty education in female students' courses. In addition, community health nurses are suggested to include this training in their programs.